APPENDIX 01: Assessment of Morphological Dynamics in Ibajay, Aklan Coast using Delft3D Numerical Simulation - Talosig, Ariston (Philippine Engineering Journal; Vol 45 No 01 (2024), 2024)
Summary of Data